2018
DOI: 10.31254/phyto.2018.7504
|View full text |Cite
|
Sign up to set email alerts
|

Resistance modulation studies of vernolide from Vernonia colorata (Drake) on ciprofloxacin, amoxicillin, tetracycline and erythromycin

Abstract: Resistance modulatory activities of natural products on traditional antibiotics have gained scientific interest in recent years. This is aimed at maximizing antimicrobial potency with major strides in curbing microbial resistance and leading to potential drug discovery. The antimicrobial activity of vernolide, a compound isolated from Vernonia colorata was investigated following its forklore use as antibiotic. The compound Vernolide was isolated from the leaves of Vernonia colorata and the identity was confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…These results are in agreement with those of Siaka [16] except for the flavonoids which was not found in our study. Studies have shown that methanolic and ethanolic extracts of Vernonia colorata leaves contain alkaloids and flavonoids [5,7,13]. The absence of alkaloids and flavonoids in the aqueous extract could be explained by the type of extraction used and also by the existence of chemotype within the species of Vernonia colorara [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in agreement with those of Siaka [16] except for the flavonoids which was not found in our study. Studies have shown that methanolic and ethanolic extracts of Vernonia colorata leaves contain alkaloids and flavonoids [5,7,13]. The absence of alkaloids and flavonoids in the aqueous extract could be explained by the type of extraction used and also by the existence of chemotype within the species of Vernonia colorara [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The presence in AEVC of the compounds such as, phenols, triterpenes, saponoids, glycosides, steroids, whose main properties are antiplasmodial, antioxidant, antibacterial and anti-inflammatory and hepatoprotective and antimicrobial, would justify its traditional use for the treatment of certain diseases [8,9,13]. Saponosides are also known to help lower blood cholesterol levels and reduce the incidence of cardiovascular disease [5]. Triterpenoids exhibit cytotoxicity against a variety of tumor cells as well as anticancer properties [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… (2012),Paul et al (2018),Alara et al (2019),Adebayo et al (2014),Aremu et al (2018),Adu et al (2018),Zubairu et al (2019). Oluyege (2019),Momoh et al (2012),Ogunnowo and Alao-Sanni (2010),Okeke et al (2015),Johnson et al (2015),Ali et al (2019),Udochukwu et al (2015) RootTula et al (2012),Inusa et al (2018),Oluyege (2019),Okeke et al (2015, Johnson et al (2015), Udochukwu et al -Sanni (2010), Tula et al (2012), Alara et al (2019), Adebayo et al (2014), Aremu et al (2018), Adu et al (2018), Zubairu et al (2019), Momoh et al (2012), Johnson et al (2015), Udochukwu et al -Sanni (2010), Tula et al (2012), Kaur et al (2019), Paul et al (2018), Alara et al (2019), Adebayo et al (2014), Aremu et al (2018), Adu et al (2018), Zubairu et al (2019), Oluyege (2019), Momoh et al (2012), Okeke et al (2015), Johnson et al (2015), Ali et al (2019), Udochukwu et al (2015) Root Tula et al (2012), Inusa et al (2018), Okeke et al (2015), Andrew (-Sanni (2010), Tula et al (2012), Kaur et al (2019), Paul et al (2018), Adebayo et al (2014), Aremu et al (2018), Zubairu et al (2019), Oluyege (2019), Momoh et al (2012), Okeke et al (2015), Johnson et al (2015), Ali et al (2019), Udochukwu et al (2015) (Continued on following page) Frontiers in Natural Products frontiersin.org…”
mentioning
confidence: 99%